Enhancing Digital Literacy and Biology Understanding through Android-Based Learning Media: A Kodular Platform Development and Evaluation - Ahmad Yani; Syamsu Rijal; Rismawati Rismawati; Dyah Anisa Kismiati; Astuti Muh Amin (AL-ISHLAH: Jurnal Pendidikan, 2025)
Traditional biology instruction often neglects digital literacy development, despite its increasing importance in 21st-century education. There is a pressing need for integrated learning tools that enhance both biological understanding and digital competencies.This study aimed to design and evaluate an Android-based biology learning media using the Kodular platform. A Research and Development (RD) approach was adopted, following the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). Sixteen grade XI students from Senior High School 2 Wajo were selected through random sampling. Data collection involved expert validation sheets, practicality and effectiveness questionnaires, and digital literacy tests.The developed media achieved high expert validation scores (82.33%) and was rated highly practical (82.5%). Paired pre-test and post-test results showed significant improvements in both biology comprehension (41.8%) and digital literacy (39.4%). Additionally, 94% of students reported that the media was effective in enhancing their engagement and understanding of the subject matter.The Kodular-based learning media proved to be an effective tool for fostering student motivation, improving conceptual understanding, and developing digital skills. Its interactive features—such as videos, animations, and quizzes—addressed common limitations in traditional instruction. The design's scalability also makes it adaptable to other STEM subjects with minimal content modification.Kodular-based media offers a flexible, user-friendly, and pedagogically sound approach to integrating digital literacy and subject learning, supporting students’ preparedness for the digital era.